Innocent or Noninnocent Interactions of the Cations on Spin-Frustrated Lindqvist Hexavanadate: Structural Analysis and Magnetic Properties - Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P; Gutierrez-Cutino, M; Gutierrez-Cutino, M (American Chemical Society, 2024)
We report the effect of the countercations in three crystalline networks based on a mixed-valence hexavanadate fragment containing 3 VIV and 3 VV centers and functionalized with three molecules of tris(hydroxymethyl)aminomethane, giving the polyanion [V3IVV3VO10{(OCH2)3CNH2}3]2-. The mixed-valence hexavanadate is crystallized using three different cations, obtaining [H3O]2[V3IVV3VO10{(OCH2)3CNH2}3]·6H2O, 1, Na2[V3IVV3VO10{(OCH2)3CNH2}3]·9H2O, 2, and [n-Bu4N]2[V3IVV3VO10{(OCH2)3CNH2}3]·(H2O)(DMF), 3. The structural characterization shows that 1-3 present perfect equilateral arrangements of the paramagnetic triangles of VIV, thus showing structural spin frustration. The supramolecular interaction modulates the studied magnetic properties depending on the size and distribution of the cations around the hexavanadate fragment. Theoretical calculations demonstrated that the three studied compounds present the ground state doublets degenerated. Compound 3 shows a plateau below 16 K in the χmT(T) plot, showing the S = 1/2 ground state due to the antiferromagnetic interactions in the triangle, whereas in compounds 1 and 2, the plateau is absent and the χmT product decreases near zero at 2 K. In 1 and 2, the magnetic moment decreases at low temperatures due to antiferromagnetic interactions of the spin triangles in the tetrahedral supramolecular arrangement. © 2024 American Chemical Society.